Survei Kepuasan Siswa Mengerjakan Tugas dengan Aplikasi Live Worksheet pada Pembelajaran Daring - Arsenius Sele (Ideguru: Jurnal Karya Ilmiah Guru, 2022)
This study aims to determine the level of satisfaction of students at SMA Negeri 1 Nunukan Selatan doing assignments with the Live Worksheet Application during online learning. Thus, it is hoped that teachers can choose applications that make it easier for students to do assignments. The method used is quantitative. Collecting data using the questionnaire method. This questionnaire is distributed online using the Google Form application. The instrument for measuring the level of student satisfaction consists of 10 statements; 3 statements about student participation in doing assignments using the Live Worksheet application and online learning barriers; 7 statements about the level of student satisfaction using the Live Worksheet application in doing assignments. There are 55 students or 71.43% of students who have used the Live Worksheet application while there are still 22 students or 28.57% of students who have never done assignments using the Live Worksheet application. There are 94.55% of students who have done assignments with the Live Worksheet application more than 4 times. Students experience obstacles in online learning, namely 66.23% of students have difficulty understanding the lesson, 49.35% of students lack concentration and 42.86% of the internet network is inadequate. There are 77.37% of students who are very satisfied that they agree that the Live Worksheet application should continue to be used to work on assignments in online learning, while 22.63% of students are dissatisfied so that they do not agree that the Live Worksheet application should continue to be used to work on assignments in online learning.